Purification method of pyromellitic dianhydride
By mixing the mixed gas containing phenylatic dianhydride with inert gas, and reacting with aqueous solution through a membrane contactor for hydrolysis, combined with sonication and cooling and crystallization, the efficient purification of phenylatic dianhydride is achieved, solving the problems of low yields and many by-products in the existing methods, improving the purity and yield, and being suitable for industrial production.
Patent Information
- Application Number
- CN202510017220.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing pyrolytic acid dianhydride purification method has low yields and many by-products. Although the hydrolysis purification method can improve the purity of the product, the yield is relatively low.
A mixed gas containing phenylatic dianhydride is mixed with an inert gas, reacted with an aqueous solution through a membrane contactor for hydrolysis, followed by ultrasonic treatment, cooling and crystallization and dehydration to achieve two-step purification.
The purity and yield of phenylatic acid dianhydride is improved, the efficiency of hydrolysis and purification method is improved, the process flow is simplified, and it is suitable for industrial production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of purifying pyromellitic dianhydride, and in particular to a method for purifying pyromellitic dianhydride. Background Art
[0002] Pyromellitic dianhydride (abbreviated as anhydride) is an important raw material for manufacturing special engineering materials polyimide. It can also be used to manufacture curing matting agents for epoxy resins and cross-linking agents for polyester resins. Pyromellitic dianhydride plays an irreplaceable role in the synthesis of polymers and is widely used in many fields such as electrochemistry and photocatalysis.
[0003] At present, the gas phase catalytic oxidation method is mainly used in the industry to prepare pyromellitic anhydride. Most of them use durene as raw material, air as oxidant, and supported vanadium neodymium oxide as catalyst to prepare pyromellitic anhydride through catalytic oxidation reaction in a fixed bed reactor. This process has low yield and many by-products, so it is necessary to purify and refine the crude product. Hydrolysis refining method is a widely used purification and refining method, which has the advantage of high product purity, but low yield.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The invention provides a method for purifying pyromellitic dianhydride, aiming to improve the purity and yield of pyromellitic dianhydride.
[0006] The present invention is achieved in that:
[0007] A method for purifying pyromellitic dianhydride comprises the following steps:
[0008] (1) mixing a mixed gas containing pyromellitic dianhydride and an inert gas to obtain a mixed gas flow;
[0009] (2) passing the mixed gas flow into an aqueous solution through a membrane contactor for hydrolysis reaction, and then separating the solid and the liquid to obtain a pre-crystallization liquid;
[0010] (3) subjecting the pre-crystallization liquid to ultrasonic treatment, cooling crystallization, and solid-liquid separation to obtain pyromellitic acid crystals;
[0011] (4) Dehydrating the pyromellitic acid crystals to obtain primary purified pyromellitic dianhydride.
[0012] In some embodiments, the once purified pyromellitic dianhydride is subjected to sublimation treatment to obtain pure pyromellitic dianhydride.
[0013] In some embodiments, the ultrasonic treatment refers to ultrasonicating the pre-crystallization solution at a temperature of 90-100° C., stopping the ultrasonication when the turbidity reaches 200-900 NTU, and performing cooling crystallization.
[0014] In some embodiments, the temperature reduction crystallization refers to cooling to 20° C. at a rate of 1 to 3° C. / min and then standing for 8 to 12 hours, and then cooling to 5 to 12° C. and standing for 2 to 4 hours.
[0015] In some embodiments, the mixed gas containing pyromellitic anhydride is a hot gas flow generated when pyromellitic anhydride is synthesized by gas-phase oxidation of tetramethylbenzene as a raw material; in other embodiments, the mixed gas containing pyromellitic anhydride is a hot gas flow obtained by heating and sublimating crude pyromellitic anhydride.
[0016] In some embodiments, the inert gas is at least one of nitrogen, air, and argon.
[0017] In some embodiments, the mixing ratio of the inert gas to the mixed gas containing pyromellitic dianhydride is 70 vt% to 90 vt%: 10 vt% to 30 vt%.
[0018] In some embodiments, the temperature of the mixed gas stream is 130-190°C.
[0019] In some embodiments, the mixing ratio of the mixed gas flow to the aqueous solution is 1 kg: 2-6 L.
[0020] In some embodiments, the membrane pore size in the membrane contactor is 500-2000 nm.
[0021] In some embodiments, the temperature of the hydrolysis reaction is 90-100° C., the reaction pressure is 0.1-0.3 MPa, and the reaction time is 1-2 h.
[0022] In some embodiments, the ultrasonic treatment time is 0.5 to 1 h.
[0023] In some embodiments, the frequency of sonication is between 20 and 200 kHz.
[0024] In some embodiments, the dehydration is performed under vacuum at a temperature of 220-250°C.
[0025] In some embodiments, the sublimation treatment refers to sublimating the primary purified pyromellitic dianhydride at 230-260° C. and −0.09 MPa, and the vaporized pyromellitic dianhydride is captured in a receiver.
[0026] The present invention has the following beneficial effects:
[0027] The present invention improves the hydrolysis refining method, uses an inert gas with a relatively low temperature to flow in parallel with a mixed gas (crude product) containing pyromellitic dianhydride, preliminarily cools the mixed gas and increases the gas pressure, and then passes the mixed gas through a membrane contactor and into an aqueous solution. Under the diversion of the membrane contactor, the mixed gas flow forms micron-sized bubbles that are blown into the aqueous solution, effectively enhancing the heat exchange efficiency and the hydrolysis efficiency, thereby improving the yield.
[0028] The present invention also improves the crystallization process of pyromellitic acid to improve the crystallization efficiency and crystal purity. The cavitation effect produced by ultrasonic treatment of the pre-crystallization liquid is beneficial to increasing the nucleation speed, thereby accelerating the crystallization, and obtaining fine and uniform crystal grain products, thereby helping to avoid the crystal grains sticking to the kettle wall and being difficult to collect, and also helping to avoid the entrainment of impurities, and more beneficial to improving the dehydration efficiency.
[0029] The purification method provided by the invention improves the efficiency and yield of a hydrolysis refining method. Through two-step purification, the obtained pyromellitic dianhydride has high purity, and the method is simple and suitable for industrial production. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0032] Reference to "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments.
[0033] In the embodiment of the present application, the term "or / and" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A or / and B can represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0034] In addition, the character “ / ” in this article generally indicates that the previous and next associated objects are in an “or” relationship.
[0035] In the embodiments of the present application, "multiple" means more than two (including two). Similarly, "multiple groups" means more than two groups (including two groups), and "multi-layer" means more than two layers (including two layers), unless otherwise clearly specified and limited.
[0036] In the embodiments of the present application, "at least one" means one or more than one.
[0037] Those skilled in the art may understand the specific meanings of the above terms in the embodiments of the present application according to specific circumstances.
[0038] The present invention provides a method for purifying pyromellitic dianhydride, comprising the following steps:
[0039] (1) mixing a mixed gas containing pyromellitic dianhydride and an inert gas to obtain a mixed gas flow;
[0040] (2) passing the mixed gas flow into an aqueous solution through a membrane contactor for hydrolysis reaction, and then separating the solid and the liquid to obtain a pre-crystallization liquid;
[0041] (3) subjecting the pre-crystallization liquid to ultrasonic treatment, cooling crystallization, and solid-liquid separation to obtain pyromellitic acid crystals;
[0042] (4) Dehydrating the pyromellitic acid crystals to obtain primary purified pyromellitic dianhydride.
[0043] The present invention first mixes a mixed gas containing pyromellitic dianhydride at a temperature of 190° C. to 230° C. with an inert gas. On the one hand, the mixed gas is initially cooled by the inert gas to prevent overheating and boiling of the aqueous solution. On the other hand, the mixed gas is diluted by the inert gas to facilitate pressurization so that it passes through a membrane contactor and promotes the dissolution of the mixed gas in water.
[0044] The present invention allows a mixed airflow to pass through a membrane contactor and mix it with an aqueous solution before entering a hydrolysis reactor. The membrane contactor contains a hollow fiber membrane, and the aqueous solution enters a liquid channel of the membrane contactor through an infusion pump. The mixed airflow enters a gas channel of the membrane contactor through a gas mass flowmeter, and the mixed airflow in the membrane contactor is bubbled through a membrane and mixed with the aqueous solution to obtain a soda-water mixture containing a large number of micron-sized bubbles, and then is introduced into the aqueous solution in the reactor. In this way, the mass transfer area and mass transfer efficiency of gas and liquid can be greatly improved, and the solubility of pyromellitic anhydride in water can be improved, thereby accelerating the hydrolysis reaction; the faster the hydrolysis reaction, the higher the efficiency, and the more conducive to the formation of pyromellitic acid crystals with high purity and high yield.
[0045] In some embodiments, the purified pyromellitic dianhydride is subjected to sublimation treatment to obtain pure pyromellitic dianhydride. The purified pyromellitic dianhydride obtained by the hydrolysis purification method can be further purified by sublimation to further improve the purity of pyromellitic dianhydride.
[0046] In some embodiments, the ultrasonic treatment refers to ultrasonicating the pre-crystallization solution at a temperature of 90-100° C., stopping the ultrasonication when the turbidity reaches 200-900 NTU, and performing cooling crystallization.
[0047] The invention creatively performs ultrasonic treatment on the pre-crystallization liquid and uses the turbidity of the liquid to control the ultrasonic endpoint, thereby controlling the particle size, distribution and purity of the obtained pyromellitic acid crystals. The cavitation effect produced by ultrasonic treatment of the pre-crystallization liquid is conducive to increasing the nucleation speed, thereby accelerating crystallization, and obtaining fine and uniform crystal grain products, thereby helping to avoid the crystal grains sticking to the kettle wall and being difficult to collect, and also helping to avoid entrained impurities, and more conducive to improving the dehydration and sublimation efficiency.
[0048] In the present invention, ultrasonic treatment obtains a large number of crystal nuclei, which belongs to the crystal nucleus formation stage, and then the growth of crystals is achieved in the cooling crystallization stage, which belongs to the crystal growth stage. Therefore, the present invention provides cooling the pre-crystallization liquid at a lower cooling rate to make it grow slowly, avoiding the embedding of impurities caused by excessive growth. In some embodiments, cooling crystallization refers to cooling to 20°C at 1 to 3°C / min and then standing for 8 to 12 hours, and then cooling to 5 to 12°C and standing for 2 to 4 hours. Further, cooling to a low temperature of 5 to 12°C is conducive to further improving the yield.
[0049] In some embodiments, the mixed gas containing pyromellitic anhydride is a hot gas flow generated when pyromellitic anhydride is synthesized by gas-phase oxidation of tetramethylbenzene as a raw material; in other embodiments, the mixed gas containing pyromellitic anhydride is a hot gas flow obtained by heating and sublimating crude pyromellitic anhydride.
[0050] In some embodiments, the inert gas is at least one of nitrogen, air, and argon.
[0051] In some embodiments, the mixing ratio of the inert gas to the mixed gas containing pyromellitic anhydride is 70vt% to 90vt%: 10vt% to 30vt%. The mixing ratio of the two has an impact on the mass transfer and heat transfer efficiency. If the inert gas is too little, the dissolution of pyromellitic anhydride will be reduced and the hydrolysis efficiency will be reduced; if the inert gas is too high, the production efficiency will be reduced and waste will be caused.
[0052] In some embodiments, the temperature of the mixed gas stream is 130-190°C.
[0053] In some embodiments, the mixing ratio of the mixed gas flow to the aqueous solution is 1 kg: 2-6 L.
[0054] In some embodiments, the membrane pore size in the membrane contactor is 500-2000 nm. The membrane pore size in the membrane contactor has an impact on the size of the micron-sized bubbles formed by the mixed gas flow. If the membrane pore size is larger, the bubbles are larger, reducing the contact area between gas and liquid; if the membrane pore size is smaller, the gas and liquid passing capacity decreases, reducing efficiency.
[0055] In some embodiments, the temperature of the hydrolysis reaction is 90-100° C., the reaction pressure is 0.1-0.3 MPa, and the reaction time is 1-2 h.
[0056] In some embodiments, the ultrasonic treatment time is 0.5 to 1 h.
[0057] In some embodiments, the frequency of ultrasonic treatment is 20-200 kHz.
[0058] In some embodiments, the dehydration is performed under vacuum at a temperature of 220-250°C.
[0059] In some embodiments, the sublimation treatment refers to sublimating the primary purified pyromellitic dianhydride at 230-260° C. and −0.09 MPa, and the vaporized pyromellitic dianhydride is captured in a receiver.
[0060] The scheme of the present invention is further described below with reference to specific embodiments.
[0061] Example 1
[0062] A method for purifying pyromellitic dianhydride comprises the following steps:
[0063] (1) After the durenyl is gasified, it is mixed with air and enters into a fixed bed reactor equipped with a catalyst for reaction. The mixed gas containing pyromellitic anhydride obtained by the reaction is mixed with a nitrogen gas flow to obtain a mixed gas flow with a temperature of 160±2° C.;
[0064] The mixing ratio of nitrogen and the mixed gas containing pyromellitic anhydride is 80vt%:20vt%.
[0065] (2) The mixed gas flow is mixed with a 60°C aqueous solution through a membrane contactor to form bubbles, and then introduced into the aqueous solution for hydrolysis reaction. Specifically, the aqueous solution enters the liquid channel of the membrane contactor through an infusion pump, and the mixed gas flow enters the gas channel of the membrane contactor through a gas mass flowmeter. After the mixed gas flow passes through the membrane in the membrane contactor for bubbling, the aqueous solution is mixed to obtain a soda-water mixture containing a large number of micron-sized bubbles; the membrane contactor is placed in an aqueous solution at a temperature of 80±10°C, so that the soda-water mixture is introduced into the aqueous solution; after the mixing ratio of the mixed gas flow to the aqueous solution reaches 1kg:4L, the feeding is stopped, the temperature is raised to 90°C, and the pressure is maintained at 0.2MPa for hydrolysis reaction for 1h. After the reaction is completed, it is filtered while hot to obtain a pre-crystallization liquid.
[0066] The membrane contactor is equipped with a hollow fiber membrane with an average pore size of 1 μm, the mixed air flow pressure is 0.4 MPa, and the aqueous solution pressure is 0.5 MPa.
[0067] (3) The pre-crystallization liquid was ultrasonically treated at 90°C until the turbidity of the pre-crystallization liquid was 400-500 NTU (measured by the formazine method using a German Lovibond TB350), the ultrasonic treatment was stopped, the liquid was cooled to 20°C at 2°C / min and allowed to stand for 10 h, and then the temperature was further lowered to 10°C and allowed to stand for 2 h, and the solid-liquid separation was performed to obtain pyromellitic acid crystals.
[0068] Among them, the ultrasonic frequency is 100kHz.
[0069] (4) The pyromellitic acid crystals are placed at 220° C. and −0.09 MPa in vacuum for dehydration to obtain primary purified pyromellitic acid dianhydride.
[0070] (5) The purified pyromellitic anhydride is placed in a sublimation tube, the temperature is set to 240° C., the vacuum degree is -0.09 MPa, and the vaporized pyromellitic anhydride is condensed in a receiver and collected to obtain pure pyromellitic anhydride.
[0071] Example 2
[0072] A method for purifying pyromellitic dianhydride comprises the following steps:
[0073] (1) Duromylene is gasified and mixed with air and then enters a fixed bed reactor equipped with a catalyst for reaction. The mixed gas containing pyromellitic anhydride obtained by the reaction is mixed with the air flow to obtain a mixed gas flow with a temperature of 190±2° C.;
[0074] The mixing ratio of air to the mixed gas containing pyromellitic anhydride is 70vt%:30vt%.
[0075] (2) The mixed gas flow is mixed with a 60°C aqueous solution through a membrane contactor to form bubbles, and then introduced into the aqueous solution for hydrolysis reaction. Specifically, the aqueous solution enters the liquid channel of the membrane contactor through an infusion pump, and the mixed gas flow is controlled by a gas mass flowmeter to enter the gas channel of the membrane contactor. After the mixed gas flow passes through the membrane in the membrane contactor for bubbling, the aqueous solution is mixed to obtain a soda-water mixture containing a large number of micron-sized bubbles; the membrane contactor is placed in an aqueous solution at a temperature of 80±10°C, so that the soda-water mixture is introduced into the aqueous solution; after the mixing ratio of the mixed gas flow to the aqueous solution reaches 1kg:6L, the feeding is stopped, the temperature is raised to 90°C, and the pressure is maintained at 0.1MPa for hydrolysis reaction for 2h. After the reaction is completed, it is filtered while hot to obtain a pre-crystallization liquid.
[0076] The membrane contactor is equipped with a hollow fiber membrane with an average pore size of 0.5 μm, the mixed air flow pressure is 0.4 MPa, and the aqueous solution pressure is 0.5 MPa.
[0077] (3) The pre-crystallization liquid is ultrasonically treated at 90° C. until the turbidity of the pre-crystallization liquid is 200-300 NTU, the ultrasonication is stopped, the liquid is cooled to 20° C. at 2° C. / min, and then allowed to stand for 10 h. The liquid is then further cooled to 10° C. and allowed to stand for 2 h. The solid-liquid separation is performed to obtain pyromellitic acid crystals.
[0078] Among them, the ultrasonic frequency is 50kHz.
[0079] (4) The pyromellitic acid crystals are placed at 240° C. and −0.09 MPa in vacuum for dehydration to obtain primary purified pyromellitic acid dianhydride.
[0080] (5) The purified pyromellitic anhydride is placed in a sublimation tube, the temperature is set to 260° C., the vacuum degree is -0.09 MPa, and the vaporized pyromellitic anhydride is condensed in a receiver and collected to obtain pure pyromellitic anhydride.
[0081] Example 3
[0082] (1) gasifying a crude solid pyromellitic anhydride product under a nitrogen atmosphere at 300° C. to obtain a gas containing pyromellitic anhydride and mixing it with an argon gas flow to obtain a mixed gas flow with a temperature of 130±2° C.;
[0083] The mixing ratio of argon gas to the mixed gas containing pyromellitic anhydride is 90vt%:10vt%.
[0084] (2) The mixed gas flow is mixed with a 60°C aqueous solution through a membrane contactor to form bubbles, and then introduced into the aqueous solution for hydrolysis reaction. Specifically, the aqueous solution enters the liquid channel of the membrane contactor through an infusion pump, and the mixed gas flow is controlled by a gas mass flowmeter to enter the gas channel of the membrane contactor. After the mixed gas flow passes through the membrane in the membrane contactor for bubbling, the aqueous solution is mixed to obtain a soda-water mixture containing a large number of micron-sized bubbles; the membrane contactor is placed in an aqueous solution at a temperature of 80±10°C, so that the soda-water mixture is introduced into the aqueous solution; after the mixing ratio of the mixed gas flow to the aqueous solution reaches 1kg:2L, the feeding is stopped, the temperature is raised to 90°C, and the pressure is maintained at 0.3MPa for hydrolysis reaction for 1h. After the reaction is completed, it is filtered while hot to obtain a pre-crystallization liquid.
[0085] The membrane contactor is equipped with a hollow fiber membrane with an average pore size of 2 μm, the mixed air flow pressure is 0.4 MPa, and the aqueous solution pressure is 0.5 MPa.
[0086] (3) The pre-crystallization liquid is ultrasonically treated at 90° C. until the turbidity of the pre-crystallization liquid is 800-900 NTU, the ultrasonication is stopped, the liquid is cooled to 20° C. at 2° C. / min, and then allowed to stand for 10 h. The liquid is then further cooled to 10° C. and allowed to stand for 2 h. The solid-liquid separation is performed to obtain pyromellitic acid crystals.
[0087] Among them, the ultrasonic frequency is 200kHz.
[0088] (4) The pyromellitic acid crystals are placed at 250° C. and −0.09 MPa in vacuum for dehydration to obtain primary purified pyromellitic acid dianhydride.
[0089] (5) The purified pyromellitic anhydride is placed in a sublimation tube, the temperature is set to 230° C., the vacuum degree is -0.09 MPa, and the vaporized pyromellitic anhydride is condensed in a receiver and collected to obtain pure pyromellitic anhydride.
[0090] Example 4
[0091] The difference from Example 1 is that the mixed gas containing pyromellitic anhydride in step (1) is obtained by heating and sublimating a crude solid pyromellitic anhydride, that is, the crude solid pyromellitic anhydride is vaporized at 300° C. in a nitrogen atmosphere to obtain a gas containing pyromellitic anhydride.
[0092] Example 5
[0093] The difference from Example 4 is that in step (1), the mixing ratio of nitrogen and the mixed gas containing pyromellitic anhydride is 70 vt%:30 vt%.
[0094] Example 6
[0095] The difference from Example 4 is that in step (1), the mixing ratio of nitrogen and the mixed gas containing pyromellitic dianhydride is 90 vt%:10 vt%.
[0096] Example 7
[0097] The difference from Example 4 is that the membrane contactor in step (2) is equipped with a hollow fiber membrane with an average pore size of 0.5 μm.
[0098] Example 8
[0099] The difference from Example 4 is that the membrane contactor in step (2) is equipped with a hollow fiber membrane with an average pore size of 2 μm.
[0100] Example 9
[0101] The difference from Example 4 is that in step (3), the pre-crystallization liquid is ultrasonically treated at 90° C. until the turbidity of the pre-crystallization liquid is 200-300 NTU.
[0102] Example 10
[0103] The difference from Example 4 is that in step (3), the pre-crystallization liquid is ultrasonically treated at 90° C. until the turbidity of the pre-crystallization liquid is 800-900 NTU.
[0104] Embodiment 11
[0105] The difference from Example 4 is that the ultrasonic frequency in step (3) is 50 kHz.
[0106] Example 12
[0107] The difference from Example 4 is that the ultrasonic frequency in step (3) is 200 kHz.
[0108] Comparative Example 1
[0109] The difference from Example 4 is that step (1) is omitted; in step (2), the crude solid pyromellitic anhydride is directly added to an aqueous solution at 80±10° C., and then heated and pressurized to carry out a hydrolysis reaction, the feed ratio of the crude solid pyromellitic anhydride to the aqueous solution is 1 kg:4 Lg, and other conditions remain unchanged; steps (3) to (5) remain unchanged.
[0110] Comparative Example 2
[0111] The difference from Example 4 is that step (2) does not use a membrane contactor, that is, the mixed gas flow is introduced into an aqueous solution at a temperature of 80±10° C. at a rate of 1 L / min.
[0112] Comparative Example 3
[0113] The difference from Example 4 is that the gas containing pyromellitic dianhydride is directly introduced into the membrane contactor without being mixed with an inert gas, and the gas flow pressure is 0.4 MPa.
[0114] Comparative Example 4
[0115] The difference from Example 4 is that in step (3), no ultrasonic treatment is performed, that is, the pre-crystallization liquid is cooled to 20°C at 2°C / min and allowed to stand for 10 h, then further cooled to 10°C and allowed to stand for 2 h, and solid-liquid separation is performed to obtain pyromellitic acid crystals.
[0116] Comparative Example 5
[0117] The difference from Example 4 is that in step (3), the pre-crystallization liquid is ultrasonically treated at 90° C. until the turbidity of the pre-crystallization liquid is 1500 NTU.
[0118] Test Case
[0119] The purity and yield (if any) of the pyromellitic acid crystals and pure pyromellitic dianhydride prepared in Test Examples 1 to 12 and Comparative Examples 1 to 5, as well as the particle size and distribution (if any) of the pyromellitic acid crystals were statistically analyzed and are shown in Table 1.
[0120] Table 1
[0121]
[0122] The test method is as follows:
[0123] (1) Purity: The purity of pure pyromellitic anhydride, crude pyromellitic anhydride, and pyromellitic acid crystals were tested by high performance liquid chromatography (HPLC) under the following conditions: column temperature 30°C, flow rate 0.5 mL / min, mobile phase methanol when the test object was pyromellitic anhydride, and mobile phase methanol: 0.1 wt% potassium dihydrogen phosphate = 5:1 (v / v) when the test object was pyromellitic acid. The purity was calculated based on the normalized area of the target peak in the spectrum.
[0124] (2) Yield:
[0125] ① in, are the yield and purity of crude pyromellitic dianhydride respectively; are the mass and purity of pyromellitic acid crystals; M PMDA 、M PMA are the relative molecular masses of pyromellitic dianhydride and pyromellitic acid, respectively.
[0126] ② in, are the yield and purity of pure pyromellitic dianhydride respectively; are the mass and purity of pyromellitic acid crystals; M PMDA 、M PMA are the relative molecular masses of pyromellitic dianhydride and pyromellitic acid, respectively.
[0127] (3) Particle size and its distribution: The particle size of pyromellitic acid crystals is tested in accordance with GB / T 19077.1. The average particle size refers to the number average particle size of pyromellitic acid crystals. Particle size widening coefficient (Span) = (Dv90-Dv10) / Dv50, where Dv90, Dv50 and Dv10 are the particle sizes corresponding to the cumulative volume percentages of 90%, 50% and 10%, respectively. The particle size widening coefficient can be used to evaluate the particle size distribution width of pyromellitic acid crystals.
[0128] It can be seen from the data in Table 1 that the method provided by the present invention can obtain pyromellitic acid crystals with high purity and yield, and the pyromellitic acid dianhydride obtained by further dehydration also has high purity and yield.
[0129] As can be seen from Examples 4 to 6, the mixed volume ratio of the inert gas to the mixed gas containing pyromellitic anhydride has an influence on the purity and yield of the obtained pyromellitic acid crystals, but has no significant influence on the particle size and distribution of the pyromellitic acid crystals. When the proportion of the inert gas in the mixed gas is greater, the heat and mass transfer efficiency of the gas-liquid is higher, and the hydrolysis efficiency of the pyromellitic anhydride in the mixed gas is higher, so the purity and yield of the pyromellitic acid crystals are higher.
[0130] It can be seen from Examples 4, 7, and 8 that the average pore size of the membrane contactor has an impact on the purity and yield of the obtained pyromellitic acid crystals, but has no impact on the particle size and distribution of the pyromellitic acid crystals. Specifically, the purity of the pyromellitic acid crystals increases first and then decreases with the average pore size of the membrane, and the yield decreases with the increase. The reason is that when the pore size is too large, the volume of the bubbles obtained is too large, the contact area with the liquid phase is reduced, and the mass transfer and heat transfer efficiency is reduced, thereby reducing the hydrolysis rate; when the pore size is too small, pyromellitic acid dianhydride is prone to condensation and precipitation to block the membrane pores, thereby reducing efficiency, reducing the hydrolysis rate, and reducing the yield. The lower the hydrolysis efficiency of pyromellitic acid dianhydride, the lower the purity of the pyromellitic acid crystals obtained after crystallization.
[0131] As can be seen from Examples 4, 9, and 10, controlling the turbidity of the pre-crystallization liquid after ultrasound during the ultrasonic treatment process can control the purity, particle size, and distribution of the obtained pyromellitic acid crystals. Turbidity reflects the degree of obstruction caused by suspended matter in water when light is transmitted. In the present invention, the pre-crystallization liquid after ultrasound contains a large number of fine crystal nuclei, which as suspended particles make the pre-crystallization liquid gradually turbid, and its content and particle size have an effect on turbidity. The present invention utilizes the cavitation effect generated by ultrasound to increase the nucleation rate of the pre-crystallization liquid, so that a large number of crystal nuclei are formed in a relatively short time, and with the extension of the ultrasound time and the control of the ultrasonic frequency, the pre-crystallization liquid after ultrasound can have different turbidities; further, the pre-crystallization liquid after ultrasound treatment is subjected to the subsequent cooling crystal growth stage, thereby affecting the growth of the crystals with different particle sizes and distributions. Specifically, when the turbidity of the liquid before the crystallization after ultrasound is larger, it shows that it contains a large number of crystalline particles or / and a larger particle size, these crystalline particles are grown under ultrasound, so the particle size is relatively uniform, and the saturation of pyromellitic acid in the liquid phase decreases with the increase of turbidity, so the crystal growth stage of the subsequent cooling has less influence on the morphology of the crystal, so the pyromellitic acid crystals obtained by embodiment 10 are distributed narrowly, and the particle size is relatively small; the turbidity of the liquid before the crystallization after ultrasound of embodiment 9 is relatively low, indicating that the amount of pyromellitic acid precipitated in the subsequent cooling stage is relatively large, and the stability of the cooling stage is relatively low compared to the ultrasonic process, so the pyromellitic acid crystals obtained are distributed widely, and the average particle size is relatively large. In addition, the turbidity of the liquid before the crystallization after ultrasound is higher, and the purity of the pyromellitic acid crystals obtained is also higher, indicating that ultrasound is conducive to reducing impurities from entering the crystal lattice and reducing the defects of the crystal.
[0132] As can be seen from Examples 4, 11, and 12, the ultrasonic frequency has an impact on the purity, yield, particle size, and distribution of pyromellitic acid crystals. The higher the ultrasonic frequency, the higher the purity, the higher the yield, the smaller the particle size, and the narrower the distribution. When obtaining a pre-crystallization solution after ultrasound with the same turbidity, if a higher ultrasonic frequency is used, the amount of crystals obtained is large but the particle size is small; if a lower ultrasonic frequency is used, the amount of crystals obtained is small but the particle size is large. Therefore, the higher the ultrasonic frequency, the more the number of crystal nuclei, so the particle size of the pyromellitic acid crystals finally obtained is smaller; in addition, since crystallization is a process of continuous dissolution-precipitation, when the number of crystal nuclei is large, the more precipitation sites, the more conducive to improving the yield. Generally, the lower the particle size of pyromellitic acid crystals, the lower the impurity content, because the impurity structure is similar to pyromellitic acid and is co-crystallized and embedded in the target product lattice by eutectic means, and the small grain size can reduce the probability of impurity embedding.
[0133] Compared with Comparative Example 1, Example 4 has a faster hydrolysis rate of phthalic anhydride than the solid-liquid mixing of Comparative Example 1 due to gas-liquid mixing and the use of a membrane contactor, so the purity and yield of the obtained phthalic acid are both higher. The membrane contactor can greatly increase the mass transfer area of gas and liquid and improve the hydrolysis efficiency. Therefore, Comparative Example 2 does not use a membrane contactor, so the purity and yield of the obtained phthalic acid are lower; Comparative Example 3 is not mixed with an inert gas before entering the membrane contactor relative to Example 1, so that the concentration of phthalic anhydride is too high when mixed with the membrane contactor, which is easy to cause membrane blockage and reduce the mass transfer efficiency. Both lead to a decrease in hydrolysis efficiency, and the purity and yield of the obtained phthalic acid crystals are lower. Comparative Example 4 is not ultrasonically treated, so the yield is lower, the crystal particle size is larger, and the impurity content is high. In Comparative Example 5, the turbidity of the pre-crystallization liquid after ultrasound is too high, resulting in a decrease in yield and purity and a wider particle size. The reason is that when the ultrasound time is too long, the turbidity of the pre-crystallization liquid after ultrasound is too high, that is, ultrasound treatment is continuously performed during the grain growth stage, and ultrasound accelerates the movement of molecules, thereby increasing the probability of grain collision and causing agglomeration.
[0134] The yield of pyromellitic acid dianhydride recorded in Table 1 is calculated based on its pyromellitic acid crystals as raw materials, so the smaller the average particle size of the pyromellitic acid crystals in this embodiment, the higher the purity, the narrower the distribution, and the higher the purity and yield of the obtained pyromellitic acid dianhydride. The reason is that the smaller the average particle size of the pyromellitic acid crystals and the narrower the distribution, the higher its sublimation efficiency, which is more conducive to impurity separation.
[0135] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for purifying pyromellitic dianhydride, characterized in that: The following steps are involved: (1) mixing a mixed gas containing pyromellitic dianhydride and an inert gas to obtain a mixed gas flow; (2) passing the mixed gas stream into an aqueous solution through a membrane contactor for hydrolysis reaction, followed by solid-liquid separation to obtain a pre-crystallization solution; (3) subjecting the pre-crystallization liquid to ultrasonic treatment, cooling crystallization, and solid-liquid separation to obtain pyromellitic acid crystals; (4) Dehydrating the pyromellitic acid crystals to obtain primary purified pyromellitic dianhydride.
2. The method for purifying pyromellitic dianhydride according to claim 1, wherein The once purified pyromellitic dianhydride is subjected to sublimation treatment to obtain pure pyromellitic dianhydride.
3. The method for purifying the pyromellitic dianhydride according to any one of claims 1 and 2, wherein: The ultrasonic treatment refers to ultrasonicating the pre-crystallization liquid at a temperature of 90-100° C., and stopping the ultrasonication when the turbidity reaches 200-900 NTU.
4. The method for purifying pyromellitic dianhydride according to claim 3, wherein The cooling crystallization refers to cooling to 20°C at 1-3°C / min and then standing for 8-12 hours, and then cooling to 5-12°C and standing for 2-4 hours.
5. The method for purifying pyromellitic dianhydride according to claim 1, wherein The mixed gas containing pyromellitic anhydride is a hot gas flow generated when pyromellitic anhydride is synthesized by gas phase oxidation using durene as a raw material, or / and the mixed gas containing pyromellitic anhydride is a hot gas flow obtained by heating and sublimating crude pyromellitic anhydride.
6. The method for purifying pyromellitic dianhydride according to any one of claims 1 to 3, characterized in that: The inert gas is at least one of nitrogen, air and argon; And / or, the mixing ratio of the inert gas to the mixed gas containing pyromellitic dianhydride is 70vt% to 90vt%: 10vt% to 30vt%; And / or, the temperature of the mixed airflow is 130-190°C.
7. The method for purifying pyromellitic dianhydride according to any one of claims 1 to 3, characterized in that: The mixing ratio of the mixed gas flow to the aqueous solution is 1kg:2-6L; And / or, the membrane pore size in the membrane contactor is 500-2000 nm. And / or, the temperature of the hydrolysis reaction is 90-100° C., the reaction pressure is 0.1-0.3 MPa, and the reaction time is 1-2 h.
8. The method for purifying pyromellitic dianhydride according to any one of claims 1 to 3, characterized in that: The ultrasonic treatment time is 0.5 to 1 h; And / or, the frequency of the ultrasonic treatment is 20 to 200 kHz.
9. The method for purifying pyromellitic dianhydride according to any one of claims 1 to 3, characterized in that: The dehydration is carried out under vacuum at a temperature of 220-250°C.
10. The method for purifying pyromellitic dianhydride according to any one of claims 2 to 3, characterized in that: The sublimation treatment refers to sublimating the primary purified pyromellitic dianhydride at 230-260° C. and −0.09 MPa, and the vaporized pyromellitic dianhydride is captured in a receiver.
Citation Information
Patent Citations
Method for producing pyromellitic dianhydride
CN101735232A
Hollow fiber membrane contact reactor and application of same to gas-liquid two-phase reaction
CN108114673A
Preparation method of pyromellitic acid based on porous black phosphene catalyst
CN108586227A
System and method for rapidly measuring solubility and diffusion coefficient of gas in liquid
CN109100269A
Method for efficiently capturing and purifying pyromellitic dianhydride
CN111892610A